IDENTIFICATION AND MONITORING OF FRESH WATER OUTFLOWS IN COASTAL AREAS: PILOT STUDY ON PSAHNA AREA / EVIA ISLAND - GREECE - Stefouli, M.; Tsombos, P. (Bulletin of the Geological Society of Greece, 2018)
Earth systems are interrelated in complex ways, which are inadequately understood. An improved understanding of these systems is necessary in order to develop effective policies for hydrologie management. Furthermore, the results should be communicated to decision-makers. The aim of the work has been to evaluate the applicability of the use of digital multi-temporal Landsat 5 / 7 images and aerial photography, for the mapping of local scale fresh water outflows, geological features and monitoring changes of the water outflows in coastal areas. "Psahna" map sheet (HAGS, 1977) in the Central part of Evia island in Greece has been used as pilot project area of study. Processing techniques have been applied for the: • Application of integrated image processing / GIS vector data techniques. • Image integration and creation of data fusion image products. • Automatic raster to vector conversion techniques, for the identification of the areal extent of changes in conditions of the water outflows through time and final map updating. The contribution of the remotely sensed data to the geologic / géomorphologie mapping and identification of changes of fresh water outflow through time is indicated with the processed satellite imagery for the pilot project area. Generally, the use of the remotely sensed images in map updating lies in the fact, that various hydrologie and geologic features can be mapped quickly for large areas while any temporal changes can be identified and evaluated. The satellite data seem to be a cost-effective solution for the map updating procedure. The cost to processing functions is well justifiable to a geologic / hydro-geologic-hydrologic map updating procedure. The system provides monitoring and feedback at appropriate spatial scales, using high resolution satellite remote sensing data and state of the art GIS techniques.